IMPLEMENTASI KEBIJAKAN PROGRAM ZAKAT, INFAK, DAN SEDEKAH OLEH FORUM ZIS KECAMATAN CICURUG - Ginung Pratidina; Rita Rahmawati; Anggi Hermawan; cecep wahyudin (Universitas Djuanda Bogor, 2022)
The flagship program is a program formed by the ZIS forum in the Cicurug district as an effort to alleviate poverty. The flagship program consists of the death benefit program, the health care program, the widow and elderly orphans compensation program, the street lighting program, and the mosque / mushola electricity bill payment program. The purpose of this study was to determine the implementation of ZIS flagship program policies by the ZIS forum in Cicurug District. This research uses descriptive qualitative method. The results showed that the flagship program was set as a priority scale for each ZIS management at the village / kelurahan level. The ZIS funds obtained at 60% are used for each ZIS forum at the village / kelurahan level. While as much as 40% of the funds obtained were deposited to the district level ZIS management. Factors supporting the implementation of the flagship program policy, namely the consistency of the community in running the flagship program and the consistency of the organizers of the ZIS forum in collecting and managing ZIS funds from the public. While the inhibiting factor relates to the reporting system of ZIS forum officials at the village / kelurahan level which is often late.